ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI AUDIT REPORT LAG (Studi Empiris pada Perusahaan Barang Konsumsi Non-Primer yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Muhammad Fadhlih Rusyana; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2023)
This study aims to analyze and provide empirical evidence of the effect of audit opinion, auditor reputation, audit tenure, audit committee activity, and industry specialized auditor on audit report lag. Also, profitability, firm size, leverage and liquidity as control variable. This study uses secondary data derived from the financial statements of all consumer cyclical sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The research sampling was carried out using purposive sampling method. A total of 88 companies were tested with details of 264 samples throughout the three-year research span. The analysis method used is partial least square with SmartPLS software 3.0 version. The results of this study indicate that audit opinion, audit tenure and industry specialized auditor has a negative effect, while auditor reputation and committee activity are found to have no effect.